Handbook of research on nanoemulsion applications in agriculture, food, health, and biomedical sciences - Ramalingam, Karthikeyan (IGI Global, 2022)
"This book focuses on the basic aspects of nanoemulsion, synthesis and characterization, and focuses on the different types of applications for nanoemulsions in agriculture, food, health, and biomedical sciences"